The Influence of Work Flexibility and Incentives on Performance with Job Satisfaction as a Mediating Variable on Desk Collection Employees of PT Swakarya Insan Mandiri Yogyakarta - Lukmawati, Linda; Wahyuni, Purbudi; Hikmah, Khoirul (Strata International Journal of Social Issues, 2025)
This study investigates the influence of work flexibility and incentives on employee performance, with job satisfaction as a mediating variable, focusing on Desk Collection employees at PT Swakarya Insan Mandiri Yogyakarta. Utilizing a quantitative approach, data were collected from 80 randomly selected employees out of a population of 321 using structured questionnaires measured on a Likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural models. The results indicate that work flexibility positively and significantly affects performance, while incentives exert a significant negative effect, implying a potential mismatch between incentive systems and employee expectations. Job satisfaction significantly enhances performance and mediates the relationship between incentives and performance; however, it does not significantly mediate the relationship between work flexibility and performance. These findings suggest that while work flexibility directly improves performance, poorly structured incentive systems may reduce job satisfaction and hinder performance outcomes. The study offers theoretical contributions to the literature on human resource and performance management, while also providing practical implications for HR policy improvements related to flexible work arrangements and incentive structures.